The Effect of the Impact of Digital Transformation Strategy on Financial Performance Moderated by Cognitive Conflict in Partner Companies of PT. Erdiva Daya Technology Solutions - Setiawan, Taufik; Widhianto, Chandra Wibowo (Pusat Publikasi Nusantara, 2024)
This study aims to verify whether digital transformation strategy (DTS) enhances organizational performance and to analyze the necessity of implementing DTS, considering perspectives like